The influence of non-uniform deformation on photoelectric properties of crystalline silicon - Vakulenko, O.V.; Kondratenko, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Measurements of the photoconductivity (PC) and photomagnetic effect (PME) spectra of crystalline silicon were carried out for the sample under the non-uniform bend deformation. This deformation causes a decrease of the photoconductivity spectrum drop in the short-wave region when illuminating the stretched surface. Under constant deformation conditions the PME spectrum form is changed only in the long-wave region. Obtained data are explained by diffusion length decreasing as a consequence of decreasing diffusion coefficient under the influence of a strain gradient.